Evaluation On Flow Behaviour Of Polypropylene/Kaolin Composites At High Shear Stress - Jikan, Suzi Salwah (2010)

(untitled)
In this study, Polypropylene (PP)/kaolin composite was compounded on a heated two roll-mill prior to testing via capillary rheometer in order to improve the rheological properties of the samples. Whereas, the extrudate from melt flow indexer (MFI) were analyzed to calculate their melt densities. The results showed that the melt density decreased linearly with an increase in processing temperature and it increased slightly with the addition of kaolin filler. On the other hand, for the investigation of melt flow properties, thermal behaviour, morphological analysis and viscoelastic phenomenon of PP/kaolin composite, the sample was subjected to extrusion process by means of capillary rheometer.